Orexin signaling via the orexin 1 receptor mediates operant responding for food reinforcement - Sharf, Ruth (2010)
BACKGROUND: Orexin (hypocretin) signaling is implicated in drug addiction and reward, but its role in feeding and food-motivated behavior remains unclear. METHODS: We investigated orexin’s contribution to food-reinforced instrumental responding using an orexin 1 receptor (Ox1r) antagonist, orexin −/− (OKO) and littermate wild-type (WT) mice, and RNAi-mediated knockdown of orexin. C57BL/6J (n=76) and OKO (n=39) mice were trained to nose poke for food under a variable ratio (VR) schedule of reinforcement. Once responding stabilized, a progressive ratio (PR) schedule was initiated to evaluate motivation to obtain food reinforcement. RESULTS: Blockade of Ox1r in C57BL/6J mice impaired performance under both the VR and PR schedules of reinforcement, indicating impaired motivational processes. In contrast, OKO mice initially demonstrated a delay in acquisition, but eventually achieved levels of responding similar to those observed in WT animals. Moreover, OKO mice did not differ from WT mice under a PR schedule, indicating delayed learning processes but no motivational impairments. Considering the differences between pharmacological blockade of Ox1r and the OKO mice, animals with RNAi mediated knockdown of orexin were then generated and analyzed to eliminate possible developmental effects of missing orexin. Orexin gene knockdown in the lateral hypothalamus (LH) in C57BL/6J mice resulted in blunted performance under both the VR and PR schedules, resembling data obtained following Ox1r antagonism. CONCLUSIONS: The behavior seen in OKO mice likely reflects developmental compensation often seen in mutant animals. These data suggest that activation of the Ox1r is a necessary component of food-reinforced responding and/or motivation in normal mice.